EDITORIAL - Cherulli Marçal, Alexandre; Ferreira Marques Neto, Antonio; dos Santos, Douglas Anderson; Mohamed Radwan Omar Osman, Elzahrã; Tavares Borges, Gabriela; Mendes Junior, Gilmar Jorge; Noleto Ferreira, Lennon Pedro; Möller, Mathias Alberto; Santos Lapa, Raphael; de Paula Martins Mendes, Ruth; et al. (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2012)
Editorial do volume 01, número 01, ano 2012.